Mindful Compassion Training on Elite Soccer: Effects, Roles and Associations on Flow, Psychological Distress and Thought Suppression - Carraça, Bruno (2019)
ABSTRACT: Introduction: Research on mindfulness and self-compassion has suggested that these closely related construct is also strongly related to flow, psychological distress, experiential avoidance and thought suppression. Despite the potential of this approach, there is a dearth of literature in respect to the relation and role of these constructs in the sport context, and specifically in soccer. Objectives: Current study explored relations among self-compassion, mindfulness, psychological flexibility, and psychological distress (including anxiety), thought suppression and flow state, through the implementation of Mindfulness-Based Soccer Program (MBPSoccerP) for elite athletes. Also was studied the influence of baseline psychological flexibility, self-compassion and mindfulness facets on psychological distress, anxiety, flow and thought suppression measures at post-intervention. Methods: The quasi-experimental design was a pre-/post-pilot study and paired t-tests, Pearson correlations and Hierarchical regression analyses were conducted to determine the common and unique variance in sport context predicted by these constructs and to compare their relative predictive strength in a nonclinical sample of elite soccer players -Portuguese 2º league (n=57; Mage = 25.79 years, SD = 3.3) Results: Self-compassion, mindfulness and psychological flexibility were negative associated with psychological distress (including anxiety) and thought suppression; and positively related to flow. In support, self-compassion, mindfulness and experiential avoidance explained variance beyond psychological distress (including anxiety), thought suppression and flow. Conclusions: Results suggest that mindfulness, self-compassion and psychological flexibility development may be beneficial in cultivating positive sport experience and flow state and less psychological distress and thought suppression.